2020
DOI: 10.3390/ani10040606
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Measures of Bovine Methane Emissions Recorded using a Laser Detector

Abstract: Methane (CH4) emissions represent a worldwide problem due to their direct involvement in atmospheric warming and climate change. Ruminants are among the major players in the global scenario of CH4 emissions, and CH4 emissions are a problem for feed efficiency since enteric CH4 is eructed to the detriment of milk and meat production. The collection of CH4 phenotypes at the population level is still hampered by costly and time-demanding techniques. In the present study, a laser methane detector was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, it is unclear whether this phenotype is comparable, in a physiological sense, to the one described above [35,38]. Niero et al [42] concluded that repeatability and reproducibility were better for the average of the peaks than for all CH 4 values. However, the same authors acknowledged that the average of the peaks may not be suitable to distinguish between high and low CH 4 emitters due to its lower variability [42].…”
Section: Separation Of Peaks and Troughsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, it is unclear whether this phenotype is comparable, in a physiological sense, to the one described above [35,38]. Niero et al [42] concluded that repeatability and reproducibility were better for the average of the peaks than for all CH 4 values. However, the same authors acknowledged that the average of the peaks may not be suitable to distinguish between high and low CH 4 emitters due to its lower variability [42].…”
Section: Separation Of Peaks and Troughsmentioning
confidence: 91%
“…LMD measurements were performed at different locations inside buildings: in RC, e.g., [18,36]; in free-stalls, e.g., [12,14]; in a tie-stall [17]; in the milking parlour (according to the author's experience); a weighing facility for sheep [15]; and in individual pens, e.g., [38,42]. A few studies have been conducted on pasture [31,32,43] or in other half or full outdoor locations [19].…”
Section: Locationmentioning
confidence: 99%
See 3 more Smart Citations